A systematic review of the impact of sport-based interventions on the psychological well-being of people in prison. (March 2017) - Woods, David; Breslin, Gavin; Hassan, David
Abstract: Purpose: The primary aim of this study was to review the impact of sport-based interventions (SBI) on the psychological well-being of people in prison. Secondary aims were to identify whether psychological theory of health behaviour change was included in the design and evaluation of interventions, and the inclusion of additional non-sporting components. Methods: A textual narrative synthesis followed a systematic search of six databases, based on PRISMA guidelines, and conducted during April 2016. Inclusion criteria were people in prison, aged 15 or over, involved in a facilitated SBI. The outcome was impact on psychological well-being and all study designs were considered. Search results were reduced from 10, 749 studies, to 14 (nine quantitative and five qualitative) after screening. Results: Interventions lasted from six weeks to nine months, with nine being multi-component. A positive affect on psychological well-being or related variable was reported in twelve studies. However, there were inconsistencies in measurement, a lack of baseline data and limited follow-up. Health behaviour change theories were a notable omission across the interventions. Conclusions: SBIs display a positive trend toward beneficial impact on psychological well-being within prisons. However, future studies should aim to address identified measurement inconsistencies and weak research design, and also include psychological change theory in their design. This will better enable practitioners and researchers alike to identify the key psychological mechanisms impacted and how, subsequently implementing SBIs with increased understanding and confidence in their contribution to prisoner psychological well-being. Highlights: A trend was observed for the positive impact of sport-based interventions on prisoner psychological well-being. Studies require additional baseline measures and medium to long-term follow-up. Interventions lacked evidence of the inclusion of health behaviour change theories.